Comparison of Acute Gene Expression Profiles of Islet Cells Obtained via Laser Capture Microdissection between Alloxan- and Streptozotocin-treated Rats. (August 2018) - Kato, Yuki; Masago, Yusaku; Kondo, Chiaki; Yogo, Erika; Torii, Mikinori; Hishikawa, Atsuko; Izawa, Takeshi; Kuwamura, Mitsuru; Yamate, Jyoji
To identify the molecular profiles of islets from alloxan (ALX)- and streptozotocin (STZ)-treated rats, a microarray-based global gene expression analysis was performed on frozen islets isolated via laser capture microdissection. At 6 weeks old, rats were injected with ALX (40 mg/kg) or STZ (50 or 100 mg/kg) and then euthanized 24 hr later. Histopathological analysis showed β-cell necrosis, macrophage infiltration, and islet atrophy. The extent of these changes was more notable in the STZ groups than in the ALX group. Transcriptome analysis demonstrated a significant up- or downregulation of cell cycle arrest–related genes in the p53 signaling pathway. Cyclin D2 and cyclin-dependent kinase inhibitor 1A, mediators of G1 arrest, were remarkably altered in STZ-treated rats. In contrast, cyclin-B1 and cyclin-dependent kinase 1, mediators of G2 arrest, were remarkably changed in ALX-treated rats. Genes involved in the intrinsic mitochondria-mediated apoptotic pathway were upregulated in the ALX and STZ groups. Moreover, heat-shock 70 kDA protein 1A ( Hspa1a ), Hsp90ab1, and Hsph1 were upregulated in ALX-treated rats, suggesting that ALX treatment injures β cells via endoplasmic reticulum stress. These results contribute to a better understanding of gene expression in the pathogenesis of islet toxicity.